Utilization of The Natural Resource Potential of The Kara-Suu ‎District of Kyrgyzstan in The Context of Central Asia: An Updated ‎Review - Raimberdievna , Shaimkulova Roza; Kurmanali , Matikeev; Abduvapovich , Obdunov Elmurat; Tashpolotovna , Shermatova Zharkynai; Jumabaevna , Turgunova Venera; Zhumabekovna , Artykbaeva Sonunbu (International Journal of Basic and Applied Sciences, 2025)
This article examines the utilization of the natural resource potential of the Kara-Suu district within ‎the broader context of Central Asia. Particular attention is paid to the historical stages of forest ‎landscape use from antiquity to the present. The study analyzes key factors contributing to forest ‎reduction, including economic activities, armed conflicts, and climate change. The ecological ‎consequences of deforestation and its effects on land and pasture resources are discussed. The ‎authors propose a range of measures for the sustainable use of natural resources and forest restoration ‎as part of the region’s sustainable development strategy. The urgent need to understand historical and ‎contemporary natural resource utilization patterns in Central Asia has increased because of worsening ‎environmental conditions and declining resources. The research investigates the natural resource ‎capabilities of the Kara-Suu district in Kyrgyzstan, which stands as a vital ecological and geopolitical area ‎while connecting to Central Asian environmental transformations and sustainability. The research ‎examines forest landscape utilization in Kara-Suu from ancient times until the present day while ‎analyzing its historical development. The research focuses on how economic instability and military ‎conflicts, together with growing populations and climate shifts, have transformed forest areas and land ‎use patterns. The article presents a complete sustainable natural resource management system that ‎suits the Kara-Suu area based on its research findings. The research presents evidence-based strategies ‎for forest restoration and policy interventions and community-led stewardship practices. The study ‎demonstrates how Kara-Suu can function as a model for Central Asian sustainable development ‎through its alignment of measures with regional sustainability targets‎.
Keywords: Kara-Suu District; Natural Resources; Forest Landscapes; Environmental Change; Sustainable Development; ‎Central Asia